Emotion Control in Children with Autism Through Play Therapy Using Traditional Games at Aisyiyah Bustanul Athfal Bhakti Karya Kindergarten - Mujiarti, Ika; Ritonga, Ristra Sandra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
Early childhood is a small individual figure who is growing and developing rapidly both physically, psychologically, and socially. The purpose of this study is to describe the emotional control of autistic children with play therapy using traditional game methods at Aisyiyah Bustanul Athfal Bhakti Karya Kindergarten. This type of research is qualitative research using field research. The subject of this study was a child who was diagnosed as autistic at Aisyiyah Bustanul Atfhal Bhakti Karya Kindergarten, totaling one person. The object of research is the nature of a person or who is the target and center of research. The results of the study obtained from the interview concluded that children have not been able to stabilize their own emotions where children will more often express anger over their dislike of something when playing with friends or with their siblings at home. Children will be given stages for implementing play therapy using traditional games that they like so that they can control their emotions.